2012
DOI: 10.1118/1.4712224
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the α/β for prostate cancer?

Abstract: Since last decade, the debate on the parameter which reflects prostate cancer sensitivity to fractionation in a radiotherapy treatment, the α/β, has become extensive. Unlike most tumors, the low labeling indices (LI) and large potential doubling time that characterize the prostate tumor led some authors to consider that it may behave as a late responding tissue. So far, the existing studies with regard to this subject point to a low value of α/β, around 2.7 Gy, which may be considered as a therapeutic gain in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 156 publications
3
17
0
Order By: Relevance
“…18 All of the optimized radiosensitivity values listed in Table III produced by the NM simplex algorithm are biologically plausible with tight confidence intervals. These values are in good agreement with both experimental and clinical observations reported in the literature through meta-analysis, 7,8 falling well within the bounds of the previously reported ranges. 7,9,46,47…”
Section: Iva the Optimized Input Parameters Of The Tcp Modelsupporting
confidence: 92%
See 3 more Smart Citations
“…18 All of the optimized radiosensitivity values listed in Table III produced by the NM simplex algorithm are biologically plausible with tight confidence intervals. These values are in good agreement with both experimental and clinical observations reported in the literature through meta-analysis, 7,8 falling well within the bounds of the previously reported ranges. 7,9,46,47…”
Section: Iva the Optimized Input Parameters Of The Tcp Modelsupporting
confidence: 92%
“…Another review of the clinical and experimental data regarding the radiobiological differential that might exist between prostate tumors and the late normal tissues surrounding the prostate suggested that the α/β ratio of the prostate is low, 2.7 Gy. 8 This value for α/β is similar to theᾱ/β value of 2.48 Gy in Table III. While values obtained from in vitro work are useful, there are reservations with them as tumors in vivo exist and proliferate in an environment different from those in vitro.…”
Section: Iva the Optimized Input Parameters Of The Tcp Modelsupporting
confidence: 81%
See 2 more Smart Citations
“…Trials comparing conventionally fractionated and hypofractionated EBRT were inconsistent in their results: the methods of early studies are not comparable to modern techniques, and the modern studies have rejected their hypotheses of superiority of hypofractionated EBRT. 69 Thus, although there is preclinical evidence to support a low α:β ratio for prostate cancer, multiple values have been reported (with most <3 Gy), 70 and the clinical data supporting the hypothetical evidence is lacking. 71 As of 2013, hypofractionated regimens are typically reserved for patients enrolled in clinical trials, 69 the theory of prostate cancer Limited data *2D and 3D IGRT.…”
Section: Stereotactic Body Radiotherapy (Sbrt)mentioning
confidence: 97%